2008
DOI: 10.1126/science.1161070
|View full text |Cite
|
Sign up to set email alerts
|

Helical Structures of ESCRT-III Are Disassembled by VPS4

Abstract: During intracellular membrane trafficking and remodeling, protein complexes known as the ESCRTs interact with membranes and are required for budding processes directed away from the cytosol, including the budding of intralumenal vesicles to form multivesicular bodies, for the budding of some enveloped viruses, and for daughter cell scission in cytokinesis. Here we found that the ESCRT-III proteins CHMP2A and CHMP3 could assemble in vitro into helical tubular structures that expose their membrane interaction si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
443
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 324 publications
(471 citation statements)
references
References 26 publications
(47 reference statements)
21
443
2
5
Order By: Relevance
“…Less consistent with the yeast-based mechanism, CHMP6, CHMP3, and CHMP1A/B knockdowns have little or no HIV-1 release phenotype (26,32). These differences are hard to reconcile with live-cell imaging detecting CHMP1B at bud sites (33) and with the finding that CHMP2A and CHMP3 coassemble in vitro into tubules but do not do so on their own (34). The differences in the results with yeast ESCRT-III proteins and the knockdown, imaging, and tubule formation data for human proteins called out for further investigation.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Less consistent with the yeast-based mechanism, CHMP6, CHMP3, and CHMP1A/B knockdowns have little or no HIV-1 release phenotype (26,32). These differences are hard to reconcile with live-cell imaging detecting CHMP1B at bud sites (33) and with the finding that CHMP2A and CHMP3 coassemble in vitro into tubules but do not do so on their own (34). The differences in the results with yeast ESCRT-III proteins and the knockdown, imaging, and tubule formation data for human proteins called out for further investigation.…”
mentioning
confidence: 68%
“…CHMP2A and CHMP3 coassemble into tubes in vitro that may represent structures involved in membrane neck scission (34). The yeast cognates of CHMP2 and CHMP3 are Vps2 and Vps24, which seem to preferentially heterodimerize with one another (23).…”
Section: Discussionmentioning
confidence: 99%
“…CHMP4B also has been shown to form spiral-shaped filaments when overexpressed in cells (25). In addition, in vitro studies have shown that ESCRT-III components spontaneously polymerize into spiral filaments that expose their membrane interaction sites on the surface, allowing them to bind tightly to surrounding membranes (26). A plausible model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A spiral polymer of ESCRT-III subunits forms at the bud neck to allow ILVs to pinch off into the lumen. This same membrane constriction activity of ESCRT-III that is harnessed for ILV formation on endosomes is also used for budding of retroviruses from the plasma membrane and membrane scission during cytokinesis in animal cells and some Archea (Hanson et al 2008;Lata et al 2008;Lindas et al 2008;Samson et al 2008;Wollert et al 2009;Henne et al 2012Henne et al , 2013. Before ILV scission, Ub can be removed from cargo to help replenish the cytosolic pool of Ub.…”
Section: Ubiquitin-dependent Sorting In Endocytosismentioning
confidence: 99%